Peptide purification using the chemoselective reaction between N‐(methoxy)glycine and isothiocyanato‐functionalized resin. (June 2016) - Hara, Toshiaki; Tainosyo, Akira; Kawakami, Toru; Aimoto, Saburo; Murata, Michio
Abstract : An efficient peptide purification strategy is established, comprising the selective reaction of an N‐terminal N ‐(methoxy)glycine residue of the peptide and isothiocyanato‐functionalized resins, and subsequent Edman degradation. These reactions take place in acidic media; in particular, the Edman degradation proceeds smoothly in media containing more than 50% trifluoroacetic acid (v/v). These acidic conditions offer increased solubility, making them advantageous for the purification of hydrophobic and aggregation‐prone peptides. The effectiveness of this method, together with scope and limitations, is demonstrated using model peptides and the practical purification of the loop region of the human dopamine D2 receptor long isoform (residues 240–272). Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : A novel peptide purification strategy is described using the selective reaction between N ‐(methoxy)glycine residue and arylisothiocyanato‐resin with successive Edman degradation.